Determinan Pemilahan Sampah pada Pedagang di Pasar Rumbai Kota Pekanbaru - Khairatul Annisa; Nila Puspita Sari; Herlina Susmaneli; Adriyani, Retno (LPPM Hang Tuah Pekanbaru, 2024)
Rumbai Market has not implemented waste sorting activities optimally. Garbage was still found scattered in the area around the traders' selling places. Waste that is not managed properly can cause various problems such as health problems, damage to market aesthetics, and water, soil, and air pollution. The research aims to determine the determinants of waste sorting among traders in Rumbai Market, Pekanbaru City. This type of observational quantitative analytical research with a cross-sectional design. Data analysis using univariate and bivariate (Chi-Square). The sample consisted of 131 people from 386 traders using simple random sampling. The measuring tool for data collection is a questionnaire from May to June 2022. This research shows that there is a relationship between Education (P-value = 0.000) POR = 3.980 (1.898-8.347), Knowledge (P-value = 0.000) POR = 5.048 (2.390-10.659), Attitude (P-value = 0.000) POR = 5,023 (2,367-10,656) and Means (P-value = 0,000) POR = 4,295 (2,049-9,003) with waste sorting on traders in Rumbai Market, Pekanbaru City. It is recommended that the Rumbai Market improve waste storage facilities, maximize the dissemination of information, and a systematic and appropriate waste transportation system according to its type.